Diet of the earliest modern humans in East Asia - Wu, Yan; Tao, Dawei; Wu, Xiujie; Liu, Wu; Cai, Yanjun (Frontiers in Plant Science, 2022)
Reconstructing diet can offer an improved understanding towards the origin and evolution of modern humans. However, the diet of early modern humans in East Asia is poorly understood. Starch analysis of dental calculus is harmless to precious fossil hominins and provides the most direct evidence of plant food sources in early modern human dietary records. In this paper, we examined the starch grains in dental calculus from Fuyan Cave hominins in Daoxian (South China), which were the earliest modern humans in East Asia. Our results reveal the earliest direct evidence of a hominin diet made of acorns, roots, tubers, grass seeds, and other yet-unidentified plants in marine isotope stage 5 between 120–80 ka. Our study also provides the earliest evidence that acorns may have played an important role in subsistence strategies. There may have been a long-lasting tradition of using these plants during the Late Pleistocene in China. Plant foods would have been a plentiful source of carbohydrates that greatly increased energy availability to human tissues with high glucose demands. Our study provides the earliest direct consumption of carbohydrates-rich plant resources from modern humans in China for the first time. In addition, it also helps elucidate the evolutionary advantages of early modern humans in the late Middle and early Upper Pleistocene.